EFEKTIVITAS LEMBAGA PENYELENGGARA RUMAH DUTA REVOLUSI MENTAL (RDRM) DALAM PENCEGAHAN PENANGANAN KASUS KEKERASAN DAN BULLYING ANAK DI KOTA SEMARANG - Nurayuni, Indah; Maesaroh, Maesaroh; Widowati, Nina (Journal of Public Policy and Management Review, 2024)
The Semarang City Government has established the Rumah Duta Revolusi Mental to address violence against children, but The number of child violence in Semarang City in 2020 was 71 cases, in 2021 it increased to 80 cases, an increase of 12% and in 2022 there were 136 cases or an increase of 70%. This research aims to analyze the effectiveness of the RDRM in preventing cases of child violence and bullying in Semarang City and analyzes the supporting factors that inhibit the effectiveness of the RDRM. The method used is a descriptive qualitative method. Data collection techniques through interviews, observation, documentation and literature study. The findings, namely achieving goals, integration and adaptation, show that on the prevention side, RDRM has not been effective in preventing violence and bullying because psychoeducation services have not been optimal, while on the treatment side RDRM has been said to be effective as proven by the number of clients who have been treated. Inhibiting and supporting factors the effectiveness of RDRM are organizational characteristics, environmental characteristics, employee characteristics and practical and management capabilities. The conclusion is that the prevention of violence and bullying carried out by RDRM organizing institutions has not been effective, while the handling of violence and bullying has been effective. Therefore, the recommendation is to disseminate information on internship recruitment regularly and open internships for students from the computer science category to help manage social media.